Genetic Diversity in Genus Citrullus (C. colocynthis and C. lanatus) - Choudhary, B R; Kumhar, S R (Annals of Arid Zone, 2016)
Genetic diversity was assessed among 39 genotypes of Citrullus, including 17 of Citrullus colocynthis and 22 of C. lanatus using eight characters such as seed yield plant-1 (SYPP), fruit yield plant-1 (FYPP), number of fruits plant-1 (NFPP), single fruit weight (SFW), fruit diameter (FD), seed weight fruit-1 (SWPF), number of seeds fruit-1 (NSPF) and 100-seed weight (HSW). The high genotypic (GCV) and phenotypic coefficient of variations (PCV) were noticed for HSW, NFPP and NSPF. The heritability in broad sense varied from 51.0 to 97.3%. The traits like HSW, SFW, NFPP and NSPF showed high heritability. Cluster analysis through Ward’s minimum variance method grouped the entries into seven clusters. Maximum number of 11 genotypes was included in cluster VII followed by eight each in clusters I and V, five in cluster IV, three in cluster VI and two each in clusters II and III. The group IV, comprized of five C. colocynthis genotypes, had high values for characters like SYPP, NFPP and NSPF while the cluster V, with eight C. lanatus genotypes, was superior for FYPP, SFW, SWPF and HSW. Among the characters studied, NSPF (48.2%) contributed the maximum towards the total divergence followed by SWPF (13.8%), HSW (10.1%) and FYPP (6.9%). The present study indicates greater diversity between genotypes of these two species and thus provides good chance to improve both the species through interspecific hybridization and selection for desired traits. Key words: Citrullus colocynthis, Citrullus lanatus, genetic diversity.